E3 Ubiquitin Ligases Neurobiological Mechanisms: Development to Degeneration - Upadhyay, Arun; Joshi, Vibhuti; Amanullah, Ayeman; Mishra, Ribhav; Arora, Naina; Prasad, Amit; Mishra, Amit (Frontiers in Molecular Neuroscience, 2017)
Cells regularly synthesized new proteins to replace old or damaged proteins. Deposition of various aberrant proteins in specific brain regions leads to neurodegeneration and ageing. The cellular protein quality control system (PQC) developed various defend mechanisms against the accumulation of misfolded and aggregated proteins. The mechanisms underlying the selective recognition of specific crucial protein or misfolded proteins majorly governed by quality control E3 ubiquitin ligases mediated through ubiquitin-proteasome system. Few known E3 ubiquitin ligases have shown prominent neurodevelopmental functions, but their interactions with different developmental proteins play critical roles in neurodevelopmental disorders (NDDs). Several questions are yet to be understood properly. How E3 ubiquitin ligases determine the specificity and regulate degradation of a particular substrate involved in neuronal proliferation and differentiation is certainly the one, which needs detailed investigations. Another important question is how neurodevelopmental E3 ubiquitin ligases specifically differentiate between their versatile range of substrates and timing of their functional modulations during different phases of developmental? The premise of this article is to understand how few E3 ubiquitin ligases sense major molecular events, which are crucial for human brain development from its early embryonic stages to throughout adolescence period. A better understanding of these few E3 ubiquitin ligases and their interactions with other potential proteins will provide invaluable insight into disease mechanisms to approach towards therapeutic interventions.